A FUNCTIONAL ANALYSIS OF MODERATE‐TO‐VIGOROUS PHYSICAL ACTIVITY IN YOUNG CHILDREN. Issue 1 (20th February 2013) - Larson, Tracy A.; Normand, Matthew P.; Morley, Allison J.; Miller, Bryon G.
Abstract Inadequate physical activity increases the risks related to a number of health problems in children, most notably obesity and the corresponding range of associated health problems. The purpose of the current study was to conduct a functional analysis to investigate the effects of several consequent variables on moderate‐to‐vigorous physical activity (MVPA). We observed the level of MVPA exhibited by 2 preschool children in 4 conditions: alone, attention contingent on MVPA, adult interaction contingent on MVPA, and escape from task demands contingent on MVPA. These four conditions were compared to a naturalistic baseline and to a control condition. Overall, results indicated that the children were most active when attention and interactive play were contingent on MVPA. Social environments that encourage MVPA could be arranged based on this information, with these arrangements tailored to the individual child.